Cardiac adrenergic nerve function and microvascular dysfunction in patients with cardiac syndrome X. Issue 7 (22nd January 2009) - Di Monaco, A; Bruno, I; Sestito, A; Lamendola, P; Barone, L; Bagnato, A; Nerla, R; Pisanello, C; Giordano, A; Lanza, G A; Crea, F
Abstract : Objective: To assess whether abnormalities in cardiac uptake of 123 I-metaiodobenzylguanidine (MIBG) correlate with coronary microvascular dysfunction in patients with cardiac syndrome X (CSX). Setting: University hospital. Patients: 29 patients (aged 59 (SD 7) years, 11 men) with typical CSX and a matched group of 20 healthy subjects (aged 56 (7) years, 8 men) were studied. Interventions: Planar and single photon emission computed tomography (SPECT) MIBG myocardial scintigraphy was performed in all subjects. Coronary flow response (CFR) to adenosine and to cold pressor test (CPT) in the left anterior descending (LAD) coronary artery was assessed in all CSX patients and in 12 controls by transthoracic Doppler echocardiography. Main outcome measures: Abnormalities in cardiac MIBG scintigraphy were observed in 25 CSX patients (86.2%), but in no healthy control (p<0.001). Compared to controls, CSX patients showed a lower heart/mediastinum (H/M) ratio of MIBG uptake (1.69 (0.24) vs 2.2 (0.3), p<0.001) and a higher cardiac MIBG defect score (25 (22) vs 4 (2), p = 0.002). Both CFR to adenosine (3.31 (1.1) vs 1.94 (0.6), p<0.001) and CFR to CPT (2.35 (0.5) vs 1.63 (0.4), p<0.001) were lower in CSX patients than in controls. In CSX patients, however, no correlation was found between MIBG H/M ratio and CFR to adenosine (r = 0.17; p = 0.38) and to CPT (r = −0.28; p = 0.13), as well as between MIBG uptake score in the LAD territory and CFR to adenosine (r = 0.14; p = 0.47) and to CPT (r = 0.06; p = 0.73). Conclusion: Our data show striking abnormalities in cardiac adrenergic nerve function and in coronary microvascular function in CSX patients. However, no significant relation between the two abnormalities was found. Further studies are needed to clarify the mechanisms and the role of MIBG defects in CSX patients.